PENGARUH TEORI BELAJAR VAN HIELE UNTUK MENINGKATKAN PEMAHAMAN KONSEP GEOMETRI SISWA KELAS V SDN 4 KALENRUNGE - Jafar, Muhammad; Muin, Awaluddin; Zalzabillah, Adilla (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
ABSTRACT This research is a Classroom Action Research that aims to determine the application of Van Hiele's learning theory to improve the understanding of geometry concepts of grade V students of SDN 4 Kalenrunge. The subjects in this study were all 23 fifth grade V students and the homeroom teacher of grade V. Data collection techniques used observation and tests. Data analysis techniques in this study are data reduction, describing data and drawing conclusions. The results of the study showed that the percentage of teacher activity in cycle I reached 60% (Enough), while the percentage in cycle II reached 93% (Good). The percentage of student activity in cycle I was 60% (Enough), while the percentage in cycle II reached 93% (Good). The achievement of student learning outcomes in cycle I was 15 out of 23 students completed with a learning completion percentage reaching 74% (Enough), while in cycle II there were 21 out of 23 students achieving completion with a learning completion percentage reaching 91% (Good). It can be concluded that Van Hiele's learning theory can improve the understanding of geometry concepts of fifth grade V students of SDN 4 Kalenrunge. Keywords : Van Hiele's Learning Theory, Understanding of Geometry Concepts